Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

-11 + 10(p + 1) = -16 + 5(2p + 3)

Sagot :

Answer:

p = all real numbers

Step-by-step explanation:

First distribute the numbers to the expressions inside the parenthesis

-11 + 10(p + 1) = -16 + 5(2p + 3)

-11 + 10p + 10 = -16 + 10p + 15

Then, add up the like terms

10p - 1 = 10p - 1

Add one to both sides

10p - 1 = 10p - 1

     + 1          + 1

10p = 10p

Divide both sides by 10

10p/10 = 10p/10

p = p

This means that no matter what you plug in for p, it will always be true.